A case of early neonate bovine tuberculosis in Ethiopia. Issue 1 (29th November 2020) - Mekonnen, Getnet Abie; Gumi, Balako; Berg, Stefan; Conlan, Andrew J. K.; Ameni, Gobena; Wood, James L. N.
Abstract: This report illustrates that calves may be infected with bovine tuberculosis at early age under natural conditions and progression can be rapid. Thus, testing of calves needs to be considered in any control program to reduce the risk of transmission. Abstract : This report illustrates that calves may be infected with bovine tuberculosis at early age under natural conditions and progression can be rapid. Thus, testing of calves needs to be considered in any control program to reduce the risk of transmission.